The effect of intracoronary infusion of bone marrow-derived mononuclear cells on all-cause mortality in acute myocardial infarction: the BAMI trial - Mathur, Anthony; Fernández-Avilés, Francisco; Bartunek, Jozef; Belmans, Ann; Crea, Filippo; Dowlut, Sheik; Galiñanes, Manuel; Good, Marie-Claire; Hartikainen, Juha; Hauskeller, Christine; Janssens, Stefan; Kala, Petr; et al. (European heart journal, 2020)
AIMS: Bone marrow-derived mononuclear cell (BM-MNC) therapy may improve myocardial recovery in patients following acute myocardial infarction (AMI), though existing trial results are inconsistent. METHODS AND RESULTS: Originally an open-label, multicentre Phase III trial, BAMI was designed to demonstrate the safety and efficacy of intracoronary infusion of BM-MNCs in reducing the time to all-cause mortality in patients with reduced left ventricular ejection fraction (LVEF, ≤45%) after primary angioplasty (PPCI) for ST-elevation AMI. Unexpectedly low recruitment means the trial no longer qualifies as a hypothesis-testing trial, but is instead an observational study with no definitive conclusions possible from statistical analysis. In total, 375 patients were recruited: 185 patients were randomized to the treatment arm (intracoronary infusion of BM-MNCs 2-8 days after PPCI) and 190 patients to the control arm (optimal medical therapy). All-cause mortality at 2 years was 3.26% [6 deaths; 95% confidence interval (CI): 1.48-7.12%] in the BM-MNC group and 3.82% (7 deaths; 95% CI: 1.84-7.84%) in the control group. Five patients (2.7%, 95% CI: 1.0-5.9%) in the BM-MNC group and 15 patients (8.1%, CI : 4.7-12.5%) in the control group were hospitalized for heart failure during 2 years of follow-up. Neither adverse events nor serious adverse events differed between the two groups. There were no patients hospitalized for stroke in the control group and 4 (2.2%) patients hospitalized for stroke in the BM-MNC group. CONCLUSIONS: Although BAMI is the largest trial of autologous cell-based therapy in the treatment of AMI, unexpectedly low recruitment and event rates preclude any meaningful group comparisons and interpretation of the observed results.
Keywords: výsledek terapie; transplantace kostní dřeně; kostní dřeň; infarkt myokardu; autologní transplantace; Bone Marrow Transplantation; Stroke Volume; Transplantation, Autologous; Treatment Outcome; Ventricular Function, Left; funkce levé komory srdeční; lidé; tepový objem; Humans; Bone Marrow; Myocardial Infarction